A Short Progress Report on High-Efficiency Perovskite Solar Cells - He Tang; Shengsheng He; Chuangwei Peng (Nanoscale Research Letters, 2017)
Abstract Faced with the increasingly serious energy and environmental crisis in the world nowadays, the development of renewable energy has attracted increasingly more attention of all countries. Solar energy as an abundant and cheap energy is one of the most promising renewable energy sources. While high-performance solar cells have been well developed in the last couple of decades, the high module cost largely hinders wide deployment of photovoltaic devices. In the last 10 years, this urgent demand for cost-effective solar cells greatly facilitates the research of solar cells. This paper reviews the recent development of cost-effective and high-efficient solar cell technologies. This report paper covers low-cost and high-efficiency perovskite solar cells. The development and the state-of-the-art results of perovskite solar cell technologies are also introduced.